Bio-inspired hydroxylation imidazole linked covalent organic polymers for uranium extraction from aqueous phases - Yan, Run-Han; Cui, Wei-Rong; Zhang, Cheng-Rong; Li, Xue-Jing; Huang, Juan; Jiang, Wei; Liang, Ru-Ping; Qiu, Jian-Ding (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
[Display omitted] •High selectivity imidazole was introduced as linkage in varying degree hydroxylation covalent organic polymers.•Benefiting from the introduction of hydroxyl groups, the uranium adsorption capacities were largely enhanced.•The TpDAB endowed prominent selectivity towards multiple metal ions including vanadium.•The hydroxyl groups significantly influenced the uranium coordination mechanism of imidazole functional group. Highly effective and reliable adsorbents for uranium extraction are vital significant for environmental protection and social development. Herein, inspired by the interaction between imidazole affinity ligand of histidine and uranium, a series of varying degree hydroxylation imidazole linked covalent organic polymers were developed for the first time via one step facile reaction without any post treatment between 2,4,6-triformylphloroglucinol (Tp), 2,4,6-triformylresorcinol (Bd), 2,4,6-triformylphenol (Hb) and 3,3′-diaminobenzidine (DAB), denoted as TpDAB, BdDAB, and HbDAB, respectively. Benefiting from the hierarchical structure of the covalent organic polymer and synergistic effects originating from hydroxyl groups and imidazole linkages, TpDAB, BdDAB, and HbDAB displayed as the promising adsorbents for uranium extraction with high extraction ability and fast capture kinetics. X-ray photoelectron spectroscopy results revealed that both nitrogen atoms in imidazole and oxygen atom in hydroxyl took part in uranium coordination. With the increasing of hydroxyl group amounts, TpDAB achieved highest extraction capacity of uranium. Furthermore, TpDAB with imidazole affinity group possessed eminent selectivity for uranium in the multiple metal ions solution, and especiallyovercome the unavoidable problem of vanadium interfering with amidoxime adsorption uranium. This work provided a promising uranium extraction strategy with high selectivity and easy preparation for environmental protection and human health.